The Effectiveness of Thematic Mapping in the Process of Learning in Schools - Dickmann, Frank; Diekmann-Boubaker, Nadine (Journal of Geography Education, 2010)
The reliable handling of graphically complex cartographical illustrations requires methodic skills from the users as well as high qualifications on the part of the map author. A very important aspect in this context is the suitable thematic mapping of visualization in school lessons. The results of an empirical survey show that the structural complexity of maps has got a considerable influence on the perceptive capacity. The adaption of complex contents depends on the previous knowledge of the mapreader.